2024
DOI: 10.1002/mds.29720
|View full text |Cite
|
Sign up to set email alerts
|

GNAO1 Mutations Affecting the N‐Terminal α‐Helix of Gαo Lead to Parkinsonism

Gonzalo P. Solis,
Yonika A. Larasati,
Moritz Thiel
et al.

Abstract: BackgroundPatients carrying pathogenic variants in GNAO1 present a phenotypic spectrum ranging from severe early‐onset epileptic encephalopathy and developmental delay to mild adolescent/adult‐onset dystonia. Genotype–phenotype correlation and molecular mechanisms underlying the disease remain understudied.MethodsWe analyzed the clinical course of a child carrying the novel GNAO1 mutation c.38T>C;p.Leu13Pro, and structural, biochemical, and cellular properties of the corresponding mutant Gαo—GNAO1‐encoded p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…While the study by Knight et al does not address the genotype-phenotype correlation of GNAO1 mutations ( 52 ), Dominguez-Carral et al identified Gβγ binding as the best predictor for clinical severity ( 51 ). Although we also found a correlation for the defects in Gβγ interaction, we conclude that it cannot serve as an efficient predictor of disease severity, and in fact loss of heterotrimer formation completely fails to agree with severe clinical manifestations in some cases ( 50 ). In our work, we tested such characteristics of pathogenic Gαo variants as (i) expression levels, (ii) ability to bind and hydrolyze guanine nucleotides, (iii) intracellular localization, (iv) binding to physiological interaction partners (RGS19 and Gβγ), (v) GPCR coupling, and (vi) neomorphic interactions with Ric8A and Ric8B proteins.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…While the study by Knight et al does not address the genotype-phenotype correlation of GNAO1 mutations ( 52 ), Dominguez-Carral et al identified Gβγ binding as the best predictor for clinical severity ( 51 ). Although we also found a correlation for the defects in Gβγ interaction, we conclude that it cannot serve as an efficient predictor of disease severity, and in fact loss of heterotrimer formation completely fails to agree with severe clinical manifestations in some cases ( 50 ). In our work, we tested such characteristics of pathogenic Gαo variants as (i) expression levels, (ii) ability to bind and hydrolyze guanine nucleotides, (iii) intracellular localization, (iv) binding to physiological interaction partners (RGS19 and Gβγ), (v) GPCR coupling, and (vi) neomorphic interactions with Ric8A and Ric8B proteins.…”
Section: Discussioncontrasting
confidence: 55%
“…Accordingly, the C215Y variant, as the T241_N242insPQ (c.724–8G > A) mutant recently characterized by us ( 49 ), falls into the milder end of the spectrum of GNAO1 encephalopathy with adolescent/adult onset ( 19 ). Along the same line, we recently showed that 2 GNAO1 mutations affecting the N-terminus of Gαo — L13P and L23P — lose Gβγ binding without acquiring the neomorphic Ric8 interaction, in agreement with their association with a mild parkinsonism phenotype ( 50 ).…”
Section: Discussionmentioning
confidence: 56%